Psychiatric Residue of Epilepsy Surgery: De Novo or Not. Issue 4 (July 2019) - Salpekar, Jay
Predicting De Novo Psychopathology After Epilepsy Surgery: A 3-Year Cohort Study Novais F, Pestana LC, Loureiro S, Andrea M, Figueira ML, Pimentel J. Epilepsy Behav. 2019;90:204-208. doi:10.1016/j.yebeh.2018.11.037. PMID: 30573340. Objective: The aim of this study was to determine the potential risk factors for de novo psychiatric syndromes after epilepsy surgery. Methods: Refractory epilepsy surgery candidates were recruited from our Refractory Epilepsy Reference Centre. Psychiatric evaluations were made before surgery and every year, during a 3-year follow-up period. Demographic, psychiatric, and neurological data were recorded. The types of surgeries considered were resective surgery (resection of the epileptogenic zone) and palliative surgery (deep brain stimulation of the anterior nuclei of the thalamus [ANT-DBS]). A survival analysis model was used to determine pre- and postsurgical predictors of de novo psychiatric events after surgery. Results: One hundred and six people with refractory epilepsy submitted to epilepsy surgery were included. Sixteen (15%) people developed psychiatric disorders that were never identified before surgery. Multilobar epileptogenic zone ( P = .001) and DBS of the ANT-DBS ( P = .003) were found to be significant predictors of these events. Conclusion: People with more generalized epileptogenic activity and those who undergo ANT-DBS seem to present an increased susceptibility for the development of mental disorders, after neurosurgical interventions, for the treatment of refractory epilepsy. People considered to be at higher risk should be submitted to more frequent routine psychiatric assessments."